Evaluation of diagnostic potential of CD38 in rickets - Xia, Yongjie; Ye, Xiaoshuo; Chen, Wei; You, Chao; Deng, Chao; Zhou, Yibiao (Molecular and cellular probes, 2024)
Rickets occurs in infants and children (aged 2 months to 3 years), compromising their skeletal development and damaging nervous, hematopoietic, immune, and other system functions. This study aimed to explore the significance of CD38 in rickets. The microarray dataset GSE22523 was analyzed to obtain differentially expressed genes in rickets patients. A total of 36 rickets patients and healthy controls were recruited for the study, and their blood samples were collected, followed by detecting mRNA levels of CD38 using quantitative real-time polymerase chain reaction (qRT-PCR). Moreover, the significance of CD38 in rickets patients was analyzed by receiver operating characteristic (ROC) analysis, while the correlation between CD38 and 25-hydroxy-vitamin D (25OHD)/parathyroid hormone (PTH) was analyzed with Pearson's correlation. Results showed that CD38 mRNA levels and PTH contents were significantly increased in the rickets patients while 25OHD contents were decreased. Correlation analysis indicated that CD38 was positively correlated with PTH and negatively correlated with 25OHD in both serum and plasma samples of rickets patients. Moreover, ROC analysis showed that serum CD38 was 0.9005 (95 % CI: 0.8313–0.9696), and the AUCs of plasma CD38 was 0.7215 (95 % CI: 0.6031–0.8398) in differentiating rickets patients from healthy persons, advocating serum CD38 had better diagnostic value. CD38 mRNA levels were upregulated in rickets patients and closely correlated with PTH and 25OHD contents, indicating CD38 might be a diagnostic marker of rickets patients. Further research on the diagnostic utility of CD38 is necessary for the diagnosis and treatment of ricketsin rickets in the future. •CD 38 was up-regulated in the rickets.•CD 38 was closely related to 25OHD and PTH in the serum of the rickets patients.•KEGG pathway enrichment analysis.